Influence of Panax ginseng on the Steady State Pharmacokinetic Profile of Lopinavir‐Ritonavir in Healthy Volunteers. Issue 11 (20th August 2014) - Calderón, Mónica M.; Chairez, Cheryl L.; Gordon, Lori A.; Alfaro, Raul M.; Kovacs, Joseph A.; Penzak, Scott R.
<x xml:space="preserve">Abstract</x> Study Objective Panax ginseng has been shown in preclinical studies to modulate cytochrome P450 enzymes involved in the metabolism of HIV protease inhibitors. Therefore, the purpose of this study was to determine the influence of P. ginseng on the pharmacokinetics of the HIV protease inhibitor combination lopinavir‐ritonavir (LPV‐r) in healthy volunteers. Design Single‐sequence, open‐label, single‐center pharmacokinetic investigation. Setting Government health care facility. Subjects Twelve healthy human volunteers. Measurements and Main Results Twelve healthy volunteers received LPV‐r (400–100 mg) twice/day for 29.5 days. On day 15 of LPV‐r administration, serial blood samples were collected over 12 hours for determination of lopinavir and ritonavir concentrations. On study day 16, subjects began taking P. ginseng 500 mg twice/day, which they continued for 2 weeks in combination with LPV‐r. On day 30 of LPV‐r administration, serial blood samples were again collected over 12 hours for determination of lopinavir and ritonavir concentrations. Lopinavir and ritonavir pharmacokinetic parameter values were determined using noncompartmental methods, and preadministration and postadministration ginseng values were compared using a Student t test, where p<0.05 was accepted as statistically significant. Conclusion Neither lopinavir nor ritonavir steady‐state pharmacokinetics were altered by 2 weeks of P. ginseng administration to healthy human volunteers. Thus, a clinically significant interaction between P. ginseng and LPV‐r is unlikely to occur in HIV‐infected patients who choose to take these agents concurrently. It is also unlikely that P. ginseng will interact with other ritonavir‐boosted protease inhibitor combinations, although confirmatory data are necessary.